Limits of interference with children’s intimacy. Legal regulation vs. intimacy without violence - Szwejser, Diana (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
This paper analyses some specific problems under article 200 § 1 of the Penal Code. The basic aim of my research was to give a relatively clear answer to the question about penalising an offender when he/she is just several years older than his/her victim or when the victim initiates sexual activities. Taking into consideration the decrease of age in which youths begin sexual initiation, it is important to know what the consequences of it in their emotional sphere are. By referring such observations to the problem of child sexual abuse, there is a dissonance between child’s acceptance of incursion in his/her intimacy and legal regulations. Therefore, child sexual abuse is not only a legal problem, but it also has influence on sexuality and the society, morality etc.